Analisis Kesalahan Siswa Kelas VIII Dalam Menyelesaikan Soal Uraian Matematika Di MTs Negeri Ngablak - Hendra Setiawan; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2018)
This study aims to determine the percentage of concept errors, procedural errors, computational errors, and to determine the most dominant error in solving the problem of mathematics description of students of grade VIII B MTs Negeri Ngablak Academic Year 2017/2018. The object of this study is the student's mistake in solving the problem description of the subject matter of the function. The type of this research is descriptive qualitative. Data collection techniques use test techniques and interview techniques. The test instrument is in the form of a description test of 5 questions. Of the five questions are declared valid and reliable. The result of the research shows that students of MTs Negeri Ngablak do average error of concept equal to 73,54% with high category, mean of procedural error equal to 30,08% with low category, and mean of computation error equal to 26,21% with category low. The most dominant type of error in the solution of the problems done by students of grade VIII B MTs Negeri Ngablak is a concept error with a percentage of 73.54%. Suggested to the teacher when solving the math problem must be complete and the teacher must provide instruction to the students that the importance in solving the problem to write the answers in accordance with the correct and proper procedures.